Augmented reality-supported artistic anatomy instruction and studio-based figure drawing performance: a quasi-experimental embedded mixed-methods study - Arif Budiman; Ary Ramadhan; Nessya Fitryona; Angga Elpatsa; Syerlie Annisa; Aditya Hanum Widarsa; Harry Prasetyo; Dini Faisal; Agariadne Dwinggo Samala (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study examined the effects of augmented reality (AR)-supported artistic anatomy learning on fine arts students’ figure drawing performance in higher education and explored students’ perceptions of the usability, engagement, and pedagogical value of AR in studio-based anatomy learning. A quasi-experimental embedded mixed-methods design was employed with an experimental group receiving AR-supported artistic anatomy instruction and a control group receiving conventional instruction. Participants were 63 undergraduate fine arts students (31 experimental; 32 control). Data were collected through pre-test and post-test figure drawing tasks, a student perception questionnaire, and qualitative discussions with selected students and lecturers. Students’ drawings were assessed using a rubric covering proportion, perspective, anatomical structure, gesture, and spatial coherence. The AR-supported group showed greater improvement than the conventional group, with the largest descriptive post-test differences in perspective and spatial coherence. Students also reported high usability, engagement, and pedagogical value. Qualitative findings indicated that rotation, scaling, and multi-angle exploration helped students examine three-dimensional bodily form before translating it into two-dimensional drawings. These findings extend AR-supported anatomy research into fine arts studio pedagogy and indicate that AR can function as a complementary visual-spatial learning tool when its affordances are aligned with discipline-specific drawing tasks.